Metode Bercerita Sebagai Penanaman Pendidikan Agama Islam Pada Anak Usia Prasekolah - Istikhori Istikhori; Ridwan Agustian Nur; Mohammad Lisanuddin Ramdlani (Institut Madani Nusantara, 2021)
The purpose in this study is as follows to find out the implementation of storytelling methods in the learning process of teaching Islamic religious education in Nabila Nagrak Kindergarten and to find out the extent of the success of storytelling methods as the cultivation of Islamic religious education in Nabila Nagrak Kindergarten. This research uses a descriptive research approach. The result of this study is that Islamic religious education instilled in students through storytelling methods helps children to know and understand the teachings in Islam. So that they can practice it in everyday life.